Development, design, and conceptual issues of project zero exposure: A program to protect young children from tobacco smoke exposure - Vardavas Constantine I; Seidmann Vered; Rubenstein Uri; Tchernokovski Shosh; Rosenblum Joseph K; Winickoff Jonathan P; Noach Michal; Hovell Melbourne F; Guttman Nurit; Rosen Laura J; Klepeis Neil E; Zucker David M (BMC, 2011)
Abstract Background Tobacco smoke exposure (TSE) is a serious threat to child health. Roughly 40% of children worldwide are exposed to tobacco smoke, and the very young are often "captive smokers" in homes in which others smoke. The goal of this research project is to develop and evaluate an intervention to reduce young child tobacco smoke exposure. The objective of this paper is to document our approach to building the intervention, to describe the planned intervention, and to explore the conceptual issues regarding the intervention and its evaluation. Methods/Design This project is being developed using an iterative approach. We are currently in the middle of Stage 1. In this first stage, Intervention Development, we have already conducted a comprehensive search of the professional literature and internet resources, consulted with experts in the field, and conducted several Design Workshops. The planned intervention consists of parental group support therapy, a website to allow use of an "online/offline" approach, involvement of pediatricians, use of a video simulation game ("Dr. Cruz") to teach parents about child TSE, and personalized biochemical feedback on exposure levels. As part of this stage we will draw on a social marketing approach. We plan to use in-depth interviews and focus groups in order to identify barriers for behavior change, and to test the acceptability of program components. In Stage II, we plan to pilot the planned intervention with 5-10 groups of 10 parents each. In Stage III, we plan to implement and evaluate the intervention using a cluster randomized controlled trial with an estimated 540 participants. Discussion The major challenges in this research are twofold: building an effective intervention and measuring the effects of the intervention. Creation of an effective intervention to protect children from TSE is a challenging but sorely needed public health endeavor. We hope that our approach will contribute to building a stronger evidence base for control of child exposure to tobacco smoke. Trial registration ClinicalTrials.gov Identifier: NCT01335178